The Fate of Prisoners of War Between the Quran, Traditions of the Prophet Muhammad and Practice of the Islamic State in Iraq and Syria - Rebaz R. Khdir (European Scientific Journal, ESJ, 2017)
Humanitarian law is the law of armed conflict that has originated from the rules and costumes of the ancient religions and civilizations. Islam includes many rules that restrict war between combatants and prohibit the warfare methods cause superfluous harm. The Quran and prophet Muhammad command Muslims to release and ransom war prisoners based on their personal conditions. The Quran never encourages Muslims to enslavement neither does mention execution but Muslims often enslaved prisoners as a common phenomenon of the era and executed some few for their atrocities and dishonesty. ISIS captured many war prisoners after the commencement of its military attacks against Iraq and Syria in 2013. The group executed most of the prisoners for taking part in battle against them through shooting, beheading, hanging and burning alive. The article compares the ISIS practice with the commandments of the Quran and prophet Muhammad in respect of the fate of war prisoners.